Harnessing the diversity of a lettuce wild relative to identify anthocyanin-related genes transcriptionally responsive to drought stress - Medina-Lozano, Inés; Grimplet, Jérôme; Díaz, Aurora (Frontiers in Plant Science, 2025)
Lettuce is a crop particularly vulnerable to drought. A transcriptomic study in the variety ‘Romired’ and the wild relative Lactuca homblei was conducted to understand the increase in anthocyanins (only significant in L. homblei) in response to drought previously observed. RNA-seq revealed more differentially expressed genes (DEGs), especially upregulated, in the wild species, in which the most abundant and significant GO terms were involved in regulatory processes (including response to water). Anthocyanin synthesis was triggered in L. homblei in response to drought, with 17 genes activated out of the 36 mapped in the phenylpropanoid-flavonoid pathway compared to 7 in ‘Romired’. Nineteen candidate DEGs with the strongest change in expression and correlation with both anthocyanin content and drought were selected and validated by qPCR, all being differentially expressed only in the wild species with the two techniques. Their functions were related to anthocyanins and/or stress response and they harboured 404 and 11 polymorphisms in the wild and cultivated species, respectively. Some wild variants had high or moderate predicted impacts on the respective protein function: a transcription factor that responds to abiotic stresses, a heat shock protein involved in stomatal closure, and a phospholipase participating in anthocyanin accumulation under abiotic stress. These genetic variants could explain the differences in the gene expression patterns between the wild (significantly up/downregulated) and the cultivated (no significant changes) species. The diversity of this crop wild relative for anthocyanin-related genes involved in the response to drought could be exploited to improve lettuce resilience against some adverse climate effects.